Directive Illocutionary Speech Acts in the Dialogue of the Grandfather Character in the Animated Film Adam and the Devil (Pragmatic Study) - Desti Fauziah; Akmaliyah Akmaliyah; Yadi Mardiansyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to identify the forms of directive speech acts and explain their functions as used by the grandfather character in the animated film Adam and the Devil. This study employs a qualitative approach using a descriptive-analytical method. Data were collected through the observation and note-taking technique, which involved watching the film repeatedly and then noting down utterances containing directive elements. The data was collected using the watch-and-record technique, which involves watching the film repeatedly and then noting down utterances containing directive elements. The data was analyzed using the pragmatic matching method. The results of the study show that directive illocutionary acts in the animated film Adam and the Devil appear in six forms, including commands, requests, invitations, prohibitions, advice, and criticism. The form of advice is the most dominant. The functions identified include ordering, requiring, compelling, advising, reminding, directing, inviting, reprimanding, prohibiting, and requesting. The results of this study indicate that the language used in this film serves not only as a tool for communication but also as a medium for moral education, the reinforcement of religious values, and character development.